The integration of 1457 World map and Bing maps in WordPress - Soh, Jolinda Sing En (2016)
Historical maps provide useful and great knowledge in showing how things were in the past. They put various information together onto a graphical image. Not many historical maps are digitalised, and information are complicated to search. Making the map readable as an image and available as digitalised context would help scholars to efficiently and effectively do researches and understand the behind stories of the map. The purpose of the project is to implement a suitable solution for integrating the 1457 World Map and the Bing Maps by transcribing 56 narrative legends and 345 places name accurately. In addition, relevant information that exists in the 21st century of the textual units on the 1457 World Map were discovered. The Scrum framework is adopted as the design methodology. The solution prototype was developed on WordPress, a popular content management system which uses HTML and CSS programming language. The implementation was done using the WordPress Shortcode API and PHP language. The results were impressive as 402 map coordinates of the textual units were accurately recorded. Although results were accurate, the process was long. Text recognition technologies such as optical character recognition and semantic web technology are highly recommended for the next similar project.